Analysis of Value Added Tax in Slovakia - Varša, Marcel; Štěpánek, Pavel; Pikhart, Zdeněk; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The aim of this thesis is to analyze the collection of value added tax in Slovakia since its independence in 1993. The main idea is to compare the collection of VAT at the current moment with the selection in the past, because during last couple of years there has been a significant increase in this area. The origin of the increase can be found in changes in legislation as well as introduction of new action plan which should make VAT collection more effective and clear. I will start with an overview of the tax and continue with historical evolution of the tax in the country. In fist part I will present the changes and tools, which came up recently and may stand behind the improvement. In the other part I will compare the collection of the tax in the past and nowadays. I will also evaluate the domestic values with values of other EU countries and look closer on the level of harmonization of the tax in Slovakia and the rest of European Union.
Vedoucí práce: Pavel Štěpánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses